2009
DOI: 10.1016/j.neulet.2009.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the relationship between ApolipoproteinE and depression

Abstract: Several studies have reported an association between the ApolipoproteinE-ε4 (APOE4) allele and depression among elders. However others have failed to find an association. Since APOE4 is a well recognized risk factor for Alzheimer dementia, cognitive status may represent an important confounder between APOE4 and depression. In this investigation, we examined the relationship between the ApolipoproteinE-ε4 allele and depression among elders accounting for cognitive status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Verification of postmenopausal status was confirmed by plasma levels of follicle stimulating hormone (≥40 mIU/ml) and current estrogen usage was substantiated by pharmacy records. All study participants were cognitively intact with at least one or more of the following putative risk factors for AD: first-degree family history of AD 29, 30, presence of the apolipoprotein (APOE) ε4 allele, history of a major mood disorder (depression or bipolar disorder) 3135, and/or history of hypothyroidism 36–39. However, only women with a history of hypothyroidism were included in the study only if the hypothyroidism was treated and medically stable.…”
Section: Methodsmentioning
confidence: 99%
“…Verification of postmenopausal status was confirmed by plasma levels of follicle stimulating hormone (≥40 mIU/ml) and current estrogen usage was substantiated by pharmacy records. All study participants were cognitively intact with at least one or more of the following putative risk factors for AD: first-degree family history of AD 29, 30, presence of the apolipoprotein (APOE) ε4 allele, history of a major mood disorder (depression or bipolar disorder) 3135, and/or history of hypothyroidism 36–39. However, only women with a history of hypothyroidism were included in the study only if the hypothyroidism was treated and medically stable.…”
Section: Methodsmentioning
confidence: 99%
“…PS1 and PS2 are components of the membrane-associated ␥-secretase protease complex that cleaves the amyloid precursor protein into non-toxic A␤-(1-40) and toxic A␤-(1-42) peptides (35,38). Intriguingly, a mutation that affects the splicing of the UBQLN mRNA has been associated with increased AD risk (39). Given the links between UBQLN and neurodegenerative disease, we explored its potential functional links to TDP-43.…”
Section: Ubqln Is a Tdp-43-interacting Protein-mentioning
confidence: 99%
“…Apolipoprotein Ee4 (APOEe4) is a well-recognised risk factor for Alzheimer's disease (AD) but has also been implicated as a potential risk factor for neuropsychiatric disorders. Several studies have reported an association between APOE4 and depressive phenomenology (Slifer et al, 2009), but the pathophysiological substrate of this relationship is not yet clear. APOE is involved in the clearance of soluble amyloid b, and the e4 allele seems to be less efficient (Jiang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%